ANALISIS PROSPEK PENGEMBANGAN USAHA KOPRA DI KECAMATAN POLEANG SELATAN KABUPATEN BOMBANA - Risna, Risna; Rianda, La; Herdiansyah, Dhian (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2019)
ABSTRACT This study aims to determine the prospect of copra business development based on the type of business in the District of South Poleang, Bombana Regency.The sampling method used in this study is Proportional Classified Random Sampling